A framework of transparency initiative (TI) to fight corruption for public construction projects / Ruzaimah Mohd Nordin - Mohd Nordin, Ruzaimah (Institute of Graduate Studies, UiTM, 2015)
Transparency is defined as the open flow of information and an essential element of the Government primary approach to reduce corruption. The prime reason for dealing with corruption problem is to promote transparency for all businesses. In Malaysia, fighting corruption is one of the National Key Results Area (NKRA) under the Government Transformation Program (GTP). Corruption is a fiduciary crime that is believed to penetrate the construction sectors in countries around the world. Given the intrinsically secretive nature of corrupt activities, the construction industry has a worldwide reputation for incidences of corruption and as for Malaysia; the issue of corruption in construction is at a serious level. Despite corruption exists in every stage of project life cycle, most of the issue of corruption focused at the procurement phase. Besides, sources of corruption can be divided into technical and behavioural issues. Undoubtedly corrupt practices have a lot of adverse effects on the industry as corruption may cause inefficiency and ineffectiveness on project performance. In recent years, anti-corruption strategy has been high on agenda in many parts of the world but relatively little examines the problem in a sector specific way. Regardless of many strategies in combating corruption has been undertaken in Malaysia, there is a need to revise for a more drastic anti-corruption strategies to implement it effectively…